Developing countries as exporters of services: looking beyond success episodes - Rolf J. Langhammer (Kiel Institute of World Economics (IfW), 2000)
The paper departs from the perception that trade in services in general and developing countries' exports in services in particular are dynamic segments of world trade. Both total trade data as well as US import trade figures do not support this perception. Success episodes such as the recent increase in Indian computer and data processing services are found to be outliers. Instead, developing countries continue to rely on relatively slowly growing exports of relatively labour-abundant consumer services relating to movements of goods and persons. Thus, they have not yet benefited from innovations in the information technology sectors providing a growth momentum for producer services. Given the link between goods production and goods distribution, successful exporters of manufactures mostly overlap with successful exporters of services. It is shown that the majority of exemptions from MFN treatment concentrate on such consumer services thus impeding developing countries' export growth. In view of the vague character of commitments negotiated in the General Agreement on Trade in Services, the paper argues that for the time being overproportionate growth of service exports from developing countries will remain limited to country episodes, but will not have the same wide country coverage as growth of manufactured exports.
Keywords: F1; 330; developing countries; trade policies; international trade in private services; Dienstleistungssektor; Export; Internationaler Dienstleistungsverkehr; Nord-Süd-Beziehungen; EDV-Dienstleistung; Export; Entwicklungsländer; Indien